Ensuring Sustainable Development of Local Self-Government: Foreign Experience for Ukraine - Ladychenko, Viktor; Gulac, Olena; Yemelianenko, Karim; Danyliuk, Yurii; Kurylo, Volodymyr (European Journal of Sustainable Development, 2021)
In order to build effective democratic governance under the Council of Europe Action Plan for Ukraine, local governments and elected representatives must have the knowledge and tools to manage modern and efficient resources, and local governments in general must increase their transparency, activities to strengthen citizens' trust in local political institutions. In its ambitious plans to implement effective governance, the Government of Ukraine is working to create a modern system of local self-government that promotes the dynamic development of regions and transfers as much power as possible to the level closest to citizens - communities. The article is devoted to the issue of ensuring the sustainable development of local self-government in Ukraine on the basis of the experience of building the system of local self-government in the European countries. Foreign experience with the existing system of local governments of Ukraine is compared. Local governments are classified into representative and executive. The practice of organizing their activities is studied. Both regional and local representative bodies and municipalities were studied. Different types of individual and collegial executive bodies of local self-government of foreign countries, methods of their formation, management models are given. The real state of the results of the reform of local self-government and decentralization, as well as the administrative-territorial system in Ukraine has been established. The main positive features of the system of local self-government bodies of foreign countries are identified and options for implementing sustainable development methods for self-government of Ukraine are proposed, including through effective state control, election of key local government officials, codification of local self-government legislation and balancing the status and powers of representatives and executive bodies of local self-government.